An Exceedingly Rare Case of Liraglutide-Induced Liver Injury. (23rd August 2021) - Parvataneni, Swetha; Ramachandran, Rajarajeshwari; Then, Eric; Grantham, Tyler; Gaduputi, Vinaya
Abstract : Liraglutide is a glucagon-like peptide-1 (GLP-1) receptor agonist used for the treatment of type 2 diabetes mellitus. We are reporting the second case of liraglutide-induced liver injury, with complete resolution of liver injury after discontinuation of the drug.